A Study of Climatic Variability over Varanasi - Singh, Anamika; Singh, B.N. (National Geographical Journal of India, 2022)
Varanasi is one of the renowned educational and religious centre of international fame. It is situated in the Middle-Ganga plain having dry-sub humid climate. Climate and its variability govern the every pulse of life in an area specifically in the agrarian economy. The climatic variability is an intrinsic feature of Indian climate, which is defined as deviation or anomalies of climatic element over a given period of time from long term climatic average. Temperature and precipitation are the main climatic elements. The variability in surface temperature affects the magnitude of evapotranspiration, atmospheric moisture and precipitation, however, normal rainfall being main source of soil moisture, provides food security and it is most important for agriculture and allied sectors. Thus, the variability of rainfall is highly related to economic activities. More than 85 percent of annual totals of rainfall occur in rainy season by the Bay of Bengal branch of southwest monsoon in Varanasi district. In the present study, an attempt has been made to find out the nature and extent of climatic variability over Varanasi on the basis of climatological data available for the period of 1905 to 2005. For the purpose, co-efficient of variability and 10 years moving average trend analysis have been made and thus the result obtained has been used to analyze the climatic variability over Varanasi.